Pregled očesnega ozadja kot možna metoda za oceno srčno-žilne ogroženosti - Petek Šter, Marija (Zdravniški vestnik, 2005)
Background. The aim of this research was to find out, whether arteriolar changes, found during an eye examination, predict high risk of a cardiovascular event, independently from the cardiovascular risk factors usingthe coronary risk tables. Methods. The cross-sectional study involved 100patients: 50 consecutive patients with arterial hypertension and 50 consecutive attenders without arterial hypertension. Excluding criteria were: age younger than 40 and older than 70, diabetes, cataract or usage of eye-drops for lowering high ocular pressure. Retinal examination was performedusing the method of direct opthalmoscopy at dilated pupil. The considered retinal changes were: generalized arteriolar narrowing, focal arteriolar narrowing, arteriovenous nicking and widened ligh reflex, but we were also looking for the presence of retinopathy (hemorrhages, exudates, optic discswelling). The cardiovascular risk was calculated using tables of coronary risk. A risk of 20% or more in the next 10 years was considered as high risk for a cardiovascular event. Results. The mean age of participant was53.5 years (SD 7.6 years). 17 (17%) participants had high coronary risk (i.e. equal or higher than 20%, according to the tables of coronary risk). retinal changes were present in 54 (54%) participants, and were more common inthe group of hypertensive patients (p=0.001). In the univariate analysis allfour types of microvascular were associated with at least 20% coronary risk, but in multivariate analysis two types of retinal changes, arteriovenousnicking (OR=9.136, 95% CI from 1.696 to 49.216) and focal arteriolar narrowing (OR= 5.885, 95% CI from 1.204 to 28.758), were associatedwith high cardiovascular risk.Conclusions. Microvascular changes arecommon among middle aged people attending general practice. (Abstract trunacted at 2000 characters)
Keywords: Ambulantna oskrba; Ambulatory Care; cardiovascular disease; Coronary Disease; diagnostika; Fundus Oculi; Hipertenzija; Hypertension; kardiovaskularne bolezni; Koronarna bolezen; Mrežnica, žile; Očesno ozadje; oftalmologija; Oftalmoskopija; Ophthalmoscopy; Retinal Vessels; Risk Assessment; Tveganje, ocenjevanje